The Effect of Educational-Spiritual Intervention on The Burnout of The Parents of School Age Children with Cancer: A Randomized Controlled Clinical Trial - Nooshin Beheshtipour; Parisa Nasirpour; Shahrzad Yektatalab; Mehran Karimi; Najaf Zare (Shiraz University of Medical Sciences, 2016)
Background: Parents of children with cancer experience high levels of stress and discomfort. Religious beliefs are important sources of comfort and support for many cancer patients and their families. The present study aimed to assess the effect of educational-spiritual intervention on burnout of the parents of the children with cancer. Methods: In this randomized clinical trial, 135 parents of children with cancer were randomly assigned into intervention and control groups. Data were collected through SMBQ (Shirom and Melamed Burnout Questionnaire) from both groups, before, immediately after and one month after the intervention. Educational-spiritual programs were held for six weeks, one session every week. The data were analyzed by SPSS using independent t-test, and repeated measure ANOVA. Results: The results showed that the mean burnout score before the intervention in the intervention group was 4.28±0.61 and in the control group it was 4.23±0.50; most of the parents reported moderate to high burnout. But, there was a significant difference between the intervention and control groups immediately after and one month after the intervention (t=10.16, P<0.0001). The mean burnout score in the intervention group was less than the control group. Results also showed that there was a significant difference between the two groups in terms of parental burnout in three times of measurements (F=58.62, P<0.0001). Conclusion: This study indicated that educational-spiritual intervention was effective on reduction of the burnout of the parents of the children with cancer. Due to high burnout of most of the parents, offering such a program could be beneficial for them. More studies in this regard are recommended.